Dyslipidemia causes overestimation of plasma mitotane measurements. (10th June 2016) - Paci, Angelo; Hescot, Ségolène; Seck, Atmane; Jublanc, Christel; Mercier, Lionel; Vezzosi, Delphine; Drui, Delphine; Quinkler, Marcus; Fassnacht, Martin; Bruckert, Eric; Lombès, Marc; Leboulleux, Sophie; et al.
Summary: Mitotane ( o, p′ -DDD) is the standard treatment for advanced adrenocortical carcinoma (ACC). Monitoring of plasma mitotane levels is recommended to look for a therapeutic window between 14 and 20mg/L, but its positive predictive value requires optimization. We report the case of an ACC patient with a history of dyslipidemia treated with mitotane in whom several plasma mitotane levels >30mg/L were found together with an excellent neurological tolerance. This observation led us to compare theoretical or measured o, p′ -DDD and o, p′ -DDE levels in a series of normolipidemic and dyslipidemic plasma samples to explore potential analytical issues responsible for an overestimation of plasma mitotane levels. We demonstrate an overestimation of mitotane measurements in dyslipidemic patients. Mitotane and o, p′ -DDE measurements showed a mean 20% overestimation in hypercholesterolemic and hypertriglyceridemic plasma, compared with normolipidemic plasma. The internal standard p, p′ -DDE measurements showed a parallel decrease in hypercholesterolemic and hypertriglyceridemic plasma, suggesting a matrix effect. Finally, diluting plasma samples and/or using phospholipid removal cartridges allowed correcting such interference. Learning points: Hypercholesterolemia (HCH) and hypertriglyceridemia (HTG) induce an overestimation of plasma mitotane measurements. We propose a routine monitoring of lipidemic status. We propose optimized methodology of measurement before interpreting high plasma mitotane levels.